Penguatan Strategi Sistem Nafkah Melalui Jejaring Sosial di Kalangan Migran Minangkabau Indonesia di Malaysia - Dhina Yuliana; Zulfan Saam; Indra Suandy; Rikki Afrizal (PELANTAR PRESS, 2026)
One of the traditions of the Minang people is to